Modeling the Payment of Basic Income to Overcome Absolute Monetary Poverty, Support Unemployed Citizens and Families with Children - N. V. Bobkov; I. B. Kolmakov; V. I. Antipov; E. V. Odintsovа (Мир новой экономики)
The article is devoted to the actual problem of the introduction of universal basic income (UBI) in Russia. Taking into account the real possibilities of the Russian economy, the issues of developing models of transitional forms of UBI, the so-called “basic income (BI)” are considered for target categories of citizens. The substantiation of the possibility and expediency of modeling the effects of BI payments according to the domestic simulation model of reproduction of Russia’s GDP P1–4–2 (2022–8) is carried out. The results of predictive calculations based on this model are presented. It is shown that the additional revenues of the consolidated budget of the Russian Federation not only compensate for the initial costs of implementing the BI program, but also exceed the initial costs annually. The conclusion is made about the reality of the implementation of the “BI program” in our country. The state leadership is proposed to combine the current system of targeted social support with the introduction of BI payments to the most vulnerable households and categories of Russian citizens in order to improve the level and quality of life of the Russian population and increase consumer demand.